Impacts of plant spacing and nitrogen fertiliser on incidences and density of spotted and African pink stem borers in Tanzania. Issue 3 (3rd July 2021) - January, Bonaventure; Rwegasira, Gration. M.; Tefera, Tadele
Abstract: Nitrogen fertilisation and plant spacing hold potential for the integrated management of rice insect pests. Field experiments were conducted in Kilombero, Tanzania to evaluate the effects of plant spacing and nitrogenous fertiliser on incidences and density of spotted and African pink stem borers. A 3 × 4 × 4 factorial experiment was used in a randomized complete block design with three replications. Treatments included application of urea fertiliser at four levels (0, 40, 80, and 160 kg N ha −1 ) and spacing at four levels (10 cm × 10 cm, 15 cm × 15 cm, 20 cm × 20 cm, and 25 cm × 25 cm). Nitrogen significantly increased dead hearts by 4.8%, white heads by 2.8% and stem borer larvae density from 0 to 5.6 larvae/m 2 . Decreasing the planting density significantly increased dead hearts by 4.7%, white heads by 2.7% and stem borer larvae density from 0 to 5.4 larvae/m 2 . The interaction of nitrogen fertiliser rates and plant spacing did not affect stem borer incidences nor larvae density, but did influence the rice yield.